2012
DOI: 10.1002/term.1549
|View full text |Cite
|
Sign up to set email alerts
|

Repair of an osteochondral defect by sustained delivery of BMP-2 or TGFβ1 from a bilayered alginate-PLGA scaffold

Abstract: Regeneration of cartilage defects can be accelerated by localized delivery of appropriate growth factors (GFs) from scaffolds. In the present study we analysed the in vitro and in vivo release rates and delivery efficacies of transforming growth factor-β1 (TGFβ1) and bone morphogenetic protein-2 (BMP-2) from a bilayered system, applied for osteochondral defect repair in a rabbit model. A bone-orientated, porous PLGA cylinder was overlaid with GF containing PLGA microspheres, dispersed in an alginate matrix. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 46 publications
1
77
0
Order By: Relevance
“…1a) was prepared as previously described (Reyes et al, 2012). Briefly, the bone-directed layer (Fig.…”
Section: Preparation Of the Tri-layered Scaffoldmentioning
confidence: 99%
See 3 more Smart Citations
“…1a) was prepared as previously described (Reyes et al, 2012). Briefly, the bone-directed layer (Fig.…”
Section: Preparation Of the Tri-layered Scaffoldmentioning
confidence: 99%
“…Microsphere preparation BMP-2 loaded microspheres were prepared by a double emulsion (w/o/w) method (Hernández et al, 2012). Briefly, the first emulsion was made by vortexing 200 µL of a BMP-2 (180 μg) solution in 0.07 % poly-vinyl alcohol (PVA) with 2 mL of a PLGA (Resomer ® RG504) methylene chloride solution (50 mg/mL).…”
Section: Preparation Of the Tri-layered Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations
“…Reyes et al 142 analyzed osteochondral regeneration postimplantation of a bilayered scaffold loaded with BMP-2 or TGF-b1 and observed that the higher concentration of BMP-2 gave rise to higher quality cartilage with improved surface regularity 2 weeks postimplantation.…”
Section: 57mentioning
confidence: 99%